2016
DOI: 10.1021/acs.langmuir.6b02349
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Ions at Uncharged Insoluble Monolayers

Abstract: A method is proposed for the experimental determination of the adsorption of inorganic electrolytes at a surface covered with insoluble surfactant monolayer. This task is complicated by the fact that the change of the salt concentration alters both chemical potentials of the electrolyte and the surfactant. Our method resolves the question by combining data for the surface pressure versus area of the monolayer at several salt concentrations with data for the equilibrium spreading pressure of crystals of the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(39 citation statements)
references
References 66 publications
7
32
0
Order By: Relevance
“…determined a barrier rate constant for myristic acid [18] at pH 2. In our study [17] of dodecanol monolayers spread on pure water or concentrated aqueous electrolytes, we found that the desorption is proceeding under barrier control for the initial 1-2 minutes. The apparent disagreements in the literature regarding the mechanism of adsorption and desorption is further discussed in the review by He et al [22].…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…determined a barrier rate constant for myristic acid [18] at pH 2. In our study [17] of dodecanol monolayers spread on pure water or concentrated aqueous electrolytes, we found that the desorption is proceeding under barrier control for the initial 1-2 minutes. The apparent disagreements in the literature regarding the mechanism of adsorption and desorption is further discussed in the review by He et al [22].…”
Section: Introductionmentioning
confidence: 62%
“…The isobaric regime has been used for determination of the diffusion coefficient D of the surfactant [5] and for evaluation of its solubility [11]; to study the dissociation and the Hofmeister effect on the properties of monolayers of adsorbed acids [7]; to study the processes involved in the collapse of the monolayer [8,12]; phase transitions [14] in monolayers; interaction between adsorbed lipids and proteins [10]; and generallythe mechanism of desorption [4,6,9]. Recently, we used the isobaric regime as an auxiliary experiment to correct the  S vs. A isotherms for the material loss due to dissolution of the monolayer [17] (similarly to Motomura et al [18]).…”
Section: Introductionmentioning
confidence: 99%
“…5 in Ref. [41]). However, this effect is complicated by the direct screening of the van der Waals attraction between the hydrocarbon tails by the salt.…”
Section: Discussionmentioning
confidence: 91%
“…S1) to determine the hard-disc area s of the surfactant independently, instead of fitting it. The alcohol group is of cross-section area smaller than that of the hydrocarbon chain, so we used crystallographic data for solid alkanes [38,39] together with area of collapse of insoluble monolayers of alcohols [40,41]: these data yield an average area per molecule in a close-packed structure of  = 18.2±0.4 Å 2 . This value must be corrected by a packing factor: for hexagonal packing,  must be divided by 1.10 (the ratio between the area of a hexagon and the inscribed circle) to obtain the actual area s = 16.5±0.4 Å 2 of the hard disc.…”
Section: (I)mentioning
confidence: 99%
See 1 more Smart Citation